Dideoxy DNA sequencing reaction (Logan, Utah : Taped Technologies, 1994)
The dideoxy DNA sequencing reaction is considered to be the least labor-intensive and most practical method for routine DNA sequencing. The components of 4 sequencing reactions consisted of a DNA template annealed to a prime, Klenow DNA polymerase, deoxynucleotides, and 35S-dATP. Each of the different reactions contained one of four chain terminators - dideoxy GTP, dideoxy ATP, dideoxy TTP, or dideoxy CTP. Consequently, the lengths of the radiolabeled reaction products corresponded to every nucleotide in the sequence. The reactions were stored indefinitely in a formamide buffer until ready for sequencing.
Keywords: Base Sequence; Dideoxynucleosides; DNA -- Analysis